The role of echosounder measurement in lidar point cloud calibration - E. A. Gasińska-Kołyszko (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The calibration of the lidar point clouds over aquatic environments presents unique challenges compared to terrestrial calibration, primarily due to the refractive and reflective properties of water. This discrepancy arises due to the fact that the majority of the calibrated area is situated in a water body. In instances where a point cloud contains water, alternative methods can be employed. These include the utilization of control points located on the beach or an echosounder with a depth greater than 1m. The area was subjected to thorough research in the vicinity of Lubiatowo, where a 1.5-kilometre coastal zone was identified, with a depth of approximately 10 meters. This survey was conducted using a lidar point cloud, created in 2018 by the Austrian company Airborne Hydro Mapping (A-M) for Polish company Apeks. The Riegl Vq880g scanner was utilized in the measurement process, which involved the registration of the seabed and the adjacent land near Lubiatowo. In the immediate vicinity, the seabed was subsequently measured using the echosounder Echotrac Cv100 (Odom) of the Polish Academy of Sciences in Gdańsk. All measurements were conducted under calm sea conditions, which minimized surface interference and improved data consistency. The received data were found to be in a 3D coordinate system UTM\WGS84 ellipsoid, and appeared to be preprocessed lidar point cloud. Therefore, an investigation was made into the relationship to the echosounder measurement. It was determined that the transforms used programs such as Microstation Power Draft with Terrascan, Geokonwerter, and Microsoft Office Excel. Calibration of the lidar point cloud was primarily conducted at a depth greater than 1m, based on echosounder measurements. Initially, the adjustment lidar point cloud size was defined to enhance its accuracy.  Following the calibration process, the lidar point cloud was matched to the echosounder. The point cloud’s correction magnitude (average) ranged from -1.14m. It is imperative to measure additional data using an echosounder during the registration of lidar data. This result underscores the necessity of integrating hydroacoustic measurements for accurate registration of lidar data in submerged environments, and reinforces the importance of methodical calibration in the development of reliable coastal and bathymetric models.